2023
DOI: 10.1007/s10479-023-05267-9
|View full text |Cite
|
Sign up to set email alerts
|

Connectedness of COVID vaccination with economic policy uncertainty, oil, bonds, and sectoral equity markets: evidence from the US

Abstract: We examine the connectedness of the COVID vaccination with the economic policy uncertainty, oil, bonds, and sectoral equity markets in the US within time and frequency domain. The wavelet-based findings show the positive impact of COVID vaccination on the oil and sector indices over various frequency scales and periods. The vaccination is evidenced to lead the oil and sectoral equity markets. More specifically, we document strong connectedness of vaccinations with communication services, financials, health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…In recent years, the issues of cryptocurrency market contagion, market uncertainty, and market complexity, combined with elevated volatility in major traditional markets, have attracted much interest from academic researchers and market practitioners (Antonakakis et al 2019 ; Xu et al 2019 ; Umar and Gubareva 2020 ; Bouri et al 2021 ; Sebastião and Godinho 2021 ; Fang et al 2022 ; Ghorbel et al 2022 ; Maghyereh and Abdoh 2022 ; Mandaci and Cagli 2022 ; Ren and Lucey 2022 ; Salisu and Ogbonna 2022 ; Umar et al 2022a ; Bossman and Gubareva 2023 ; Yousaf et al 2023 ). One prominent area of research in this field centers on the risk spillover between cryptocurrencies and traditional financial markets, with a particular focus on new avenues for hedging and diversification opportunities in both directions (Hsu et al 2021 ; Zhang and He 2021 ; Attarzadeh and Balcilar 2022 ; Maitra et al 2022 ; Yousaf et al 2022 ; Bossman et al 2023a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the issues of cryptocurrency market contagion, market uncertainty, and market complexity, combined with elevated volatility in major traditional markets, have attracted much interest from academic researchers and market practitioners (Antonakakis et al 2019 ; Xu et al 2019 ; Umar and Gubareva 2020 ; Bouri et al 2021 ; Sebastião and Godinho 2021 ; Fang et al 2022 ; Ghorbel et al 2022 ; Maghyereh and Abdoh 2022 ; Mandaci and Cagli 2022 ; Ren and Lucey 2022 ; Salisu and Ogbonna 2022 ; Umar et al 2022a ; Bossman and Gubareva 2023 ; Yousaf et al 2023 ). One prominent area of research in this field centers on the risk spillover between cryptocurrencies and traditional financial markets, with a particular focus on new avenues for hedging and diversification opportunities in both directions (Hsu et al 2021 ; Zhang and He 2021 ; Attarzadeh and Balcilar 2022 ; Maitra et al 2022 ; Yousaf et al 2022 ; Bossman et al 2023a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the COVID-19 pandemic has had the greatest impact on the relationships among them. [45] examined the connectedness between the COVID vaccination and sectoral equity markets in the US. According to their findings, vaccination has positively affected the sector indices.…”
Section: Literature Reviewmentioning
confidence: 99%